Development of microsatellite markers for Hyacinth macaw (Anodorhynchus hyacinthinus) and their cross-amplification in other parrot species Genetics - Da Silva, Helder E. [UNESP]; Presti, Flavia T. [UNESP]; Wasko, Adriane P. [UNESP]; Pinhal, Danillo [UNESP] (Springer Nature, 2015)
Background: Hyacinth macaw Anodorhynchus hyacinthinus is the largest parrot of the world and is considered vulnerable to extinction due to its habitat loss and illegal trade associated to the international pet market demand. Genetic studies on this species are still incipient to generate a consistent characterization of the population dynamics and to develop appropriate conservation strategies. In this sense, microsatellite markers may support the detection of a population genetic structure for this bird species. However, at this time, none Hyacinth macaw species-specific primers for microsatellite loci have been so far established. This study aimed to develop and characterize polymorphic microsatellite markers for A. hyacinthinus and to check for their cross-amplification in other parrot species. Findings: Sequences containing repeated dinucleotide motifs were prospected and optimized from a genomic library that was enriched for microsatellites using magnetic beads. The analyses of 43-57 samples from wild individuals of three distinct Brazilian subpopulations led to the characterization of five polymorphic microsatellite loci. Allele richness per locus ranged from two to 12. Three loci exhibited observed heterozygosity values higher than 50 %, but the overall average value among all loci was close to 45 %. In addition, successful primer cross-amplification was verified in seven other investigated species of Neotropical parrots. Conclusions: The newly developed markers have shown to be potentially useful for in situ and ex situ population studies to support future conservation actions of Hyacinth macaw and other parrots.
Keywords: Conservation; Cross-species amplification; Genetic diversity; Microsatellites; Parrots